New maize germplasm introductions in Brazil - Moro, José Roberto; Naspolini Filho, Valdemar; Vianna, Ronaldo Torres; Gama, Elto Eugenio Gomes e (Pesquisa Agropecuaria Brasileira, 2014)
In 1976 many sources of new germplasm considered to have potential in Brazil were selected and introduced from CIMMYT. This material was evaluated in 51 experiments throughout Brazil in a network of national trials to determine its genetic potential. On the basis of these results, the following germplasm have potential in Brazil: Pool 21, 22, 25 and 26, Suwan DMR, Tuxpeno 1, Mezcla Tropical Blanco, Blanco Cristalino 1, Antigua x Vera Cruz 181, Mezcla Amarilla, Amarillo Cristalino, Amarillo Dentado and Subtropical, Antigua x Rep. Dominicana and Eto x Illinois. They were selected based upon high mean yield, earliness and low plant and ear height, except for Pools and Suwan DMA which were only considered for high mean yield.